1994
DOI: 10.1029/94jd01243
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of C2‐C6 hydrocarbons during the Polar Sunrise1992 Experiment: Evidence for Cl atom and Br atom chemistry

Abstract: Grab samples for nonmethane hydrocarbons (NMHCs) were collected from three sites: daily at Alert, Northwest Territories (82.5° N, 62.3° W) from January 21 to April 19, daily at an ice floe 150 km north of Alert from April 9 to 25, and on an aerial survey conducted in April over the Arctic archipelago. Insitu measurements of n‐butane and i‐pentane were also made hourly at Alert from April 2 to April 15. During the dark period (January to March), C2‐C6 hydrocarbon concentrations correlated with those of methane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
390
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 396 publications
(402 citation statements)
references
References 32 publications
(4 reference statements)
12
390
0
Order By: Relevance
“…4 shows the measured ratio of i-butane to n-butane as a function of the ratio of i-butane to propane for the pure NaNO 3 case. As discussed by Jobson et al, 170 the two butane isomers should decay at approximately the same rate if they are being removed by reaction with OH (solid line in Fig. 4).…”
Section: View Article Onlinesupporting
confidence: 52%
“…4 shows the measured ratio of i-butane to n-butane as a function of the ratio of i-butane to propane for the pure NaNO 3 case. As discussed by Jobson et al, 170 the two butane isomers should decay at approximately the same rate if they are being removed by reaction with OH (solid line in Fig. 4).…”
Section: View Article Onlinesupporting
confidence: 52%
“…However, Tang and McConnell (1996) have proposed that it might still be sufficient if it activates chain reactions involving bromide from sea salt particles accumulated on the snow pack during polar winter. Chlorine atom chemistry has also been observed simultaneously with the ozone depletion episodes (Jobson et al, 1994), supporting sea salt as the bromine source. Consistent with this, Hopper et al (1998) observed that the ozone depleting processes occurred only in air masses above sea ice.…”
mentioning
confidence: 88%
“…A final data set is taken from the Polar Sunrise Experiment 1992 field campaign at Alert, N.W.T., during the "dark" period from January to March [Jobson et al, 1994].…”
Section: Methodsmentioning
confidence: 99%